Leukemia / Lymphoma T of the adult HTLV1, a challenge for the clinic: Leucemia/linfoma T del adulto HTLV1, un desafío para el clínico - Cabrera, María Elena (2020)
Adult T-cell leukemia/lymphoma (ATL) is an aggressive disease of mature activated T cell caused by human T-cell lymphotropic virus type 1 (HTLV-1). ATL carries a bad prognosis due to intrinsic chemoresistance and severe immunosuppression. The aggressive ATL forms, acute and lymphoma, are treated with chemotherapy associated with antiretroviral agents (AZT/IFN) the acute form. However, they have failed to achieve an impact on survival, that ranges from 8-10 months, respectively. Patients with chronic and smoldering ATL forms, have a better prognosis, but long term survival is poor as well, when these patients are managed with a watchfulwaiting policy or with chemotherapy. Apparently, AZT/IFN seams to benefit these patients. Meanwhile, prevention of dissemination of HTLV-1, is a must in public health policies, performing screening in blood banks and a screening to pregnant women to reduce/avoid vertical transmission of the virus.